Occupational Prevalence of GERD in the Hospitality Sector: A Cross-Sectional Study from Belagavi District, Karnataka - Sreenikakumar, Padmaveer Puthiyidam; Sagare, Sandeep Subash; Swasthik; Gani, Vidya Parasappa (International Journal of Pharmaceutical Investigation, 2026)
Background Gastroesophageal Reflux Disease (GERD) is a prevalent gastrointestinal disorder that significantly impacts quality of life. Occupational factors such as irregular work schedules, stress, and dietary habits contribute to GERD development. Hospitality workers, due to the nature of their profession, are at an increased risk of GERD. Objectives This study aims to determine the prevalence of GERD among hospitality workers in Belagavi district, Karnataka, India, and to assess the occupational and lifestyle-related risk factors associated with the condition. Materials and Methods A cross-sectional study was conducted among 350 hospitality workers, using a validated GERD diagnostic questionnaire. Participants were selected through random sampling, and data on demographic characteristics, work schedules, dietary patterns, and GERD symptoms were collected. Statistical analysis, including Chi-square tests and logistic regression, was performed to evaluate associations between GERD and occupational factors. Results The prevalence of GERD among hospitality workers was found to be 28.57%, with mild (19.71%), moderate (4.57%), and severe (4.29%) cases identified. Irregular work hours (96.6% worked more than 10 hr/day), disrupted sleep (19.4% had less than 5 hr of sleep), and frequent consumption of restaurant meals (30.8%) were significantly associated with GERD. Female participants exhibited a higher prevalence of severe GERD (9.2%) compared to males (2.9%). Statistical analysis revealed significant associations between GERD and variables such as sleep duration (p=0.004), occupation type (p=0.013), and dietary habits (p=0.03). Conclusion The high prevalence of GERD among hospitality workers highlights the need for workplace interventions, health awareness programs, and lifestyle modifications. Addressing occupational stress, promoting structured meal breaks, and improving sleep hygiene could help mitigate GERD risk in this vulnerable population.
Keywords: Gastroesophageal reflux disease; Hospitality workers; Occupational health; Dietary habits; Lifestyle factors; Prevalence